Design of Flowline, Separator, and Slug Catcher in X Field - I Gede Dian Aryana; Muhammad Taufiq Fathaddin; Djoko Sulistyanto (Journal of Earth Energy Science, Engineering, and Technology, 2018)
The use of the pipeline is the safest method in sending oil and gas from one area to another in oil and gas transportation system. The only challenge is to keep the pressure drop in the pipeline as small as possible to avoid high pressure differences. This pressure difference can result in reduced production flow rate and affect the flow pattern in the pipeline. The condition can lead to high possibility of a slug on pipelines that drain multiphase flow. Slug becomes one of the main concerns transport processes multiphase flow in pipelines. The emergence of slug in the pipeline could cause an unstable hydrodynamic conditions will continue to affect the liquid level in the inlet separator and cause flooding in the separator. Some of the conclusions mainly on the diameter of the pipeline, the size of the slug catcher and the size of the separator obtained from the calculation based on the study of literature and simulations with software HYSIS and OLGA. Design slug catcher to accommodate the number of processes that occur in the production transportation of X oil and gas field through a pipeline 10 inches along the 12 km with 20.68 m3 volume of slug using 3 (three) finger with diameter 28 inches and length of 10 meters each. For the separation process of oil and gas in the first five (5) years of X oil and gas field  which has a high production of oil and condensate will require separator with 30 inches diameter, seam to seam height of 8.1 ft or 2.5 meters, with retention time for 2 minutes and the 3.2 slenderness ratio of the vertical separator.